BEZSTRONNOŚĆ ŚWIATOPOGLĄDOWA ORGANÓW PAŃSTWA POLSKIEGO NA PRZYKŁADZIE ORZECZENIA WSA W WARSZAWIE II SA/2293/11 – WYROK Z 20 MARCA 2012 ROKU. UWAGI O CHARAKTERZE APROBUJĄCYM - Nikołajew, Jerzy (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The subject matter of this discussion is the the administrative court’s decision on prohibition of personal data processing by the parish priest with respect to those who declared defection from the Catholic Church. First, the author examines the facts of the case and then the court’s decision in this matter. The paper refers also to the relevant national legislation, EU directives and guidelines of the Episcopate of the Catholic Church in Poland, which was in fact invoked by the administrative court. The article ends with conclusions that the said judgement is in line with the constitutional principle of the state ideological impartiality and equality of religious association.